An Ergonomic Study of The Effect of Scaling Procedure on The Musculoskeletals Problems, Workloads, and Eye Strain Among Dental Students - Sudirman, Putu Lestari; Adiatmika, I P. G.; Adiputra, I Nyoman; Tirtayasa, I Ketut (Journal of A Sustainable Global South, 2021)
Dental treatments generally need length of time period. The dental care consist of several steps and these steps should be performed in the cramped space which is patient’s mouth (oral cavity). Thus, dentists have potential on suffering for musculoskeletal injuries which may affect their quality of work. This is a descriptive study (observation and interviews) with cross-sectional approach. This study conducted observation on several ergonomic aspects include task, organizational, and environment; following with interviews on how were dental students performing scaling procedures The mean time of dental students in performing scaling was 28,38 ± 1,03 minutes, this period of time also cover all the time needed for several adjusting working positions taken by dental students on purpose to cover scaling on all of the teeth surfaces and regions. Dentists have risk for potential injuries resulted from non-ergonomic working attitude and static position. This indicated from increasing of Nordic Body Map scores after performing scaling with mean scores 13,87 ± 1,56, increasing eyes train scores up to 2,2 ± 0,27, and increasing work load which was calculated from hearth rate 23,45 ± 2,70 beats/menit. This study also assesses organizational and working environment which may affect dental students on performing scaling. The total ergonomic approach may be employed to solve the identified problems from ergonomic assessment on the scaling procedures performed by dental students at Dentistry Udayana University. Thus, it is expected that the approach can be solve the problems complained by dental students while performing scaling procedure, as well as assistant operators, patients, and others related parties without creating unnecessary side effects causing by the purposed adjustment. Index Terms — scaling, ergonomic study, dentist